Factors Indicating the Accuracy of Fetal Weight Estimation in Preterm Newborns with Normal Amniotic Fluid Volume - Onur Guralp; Nevin Tuten; Abdullah Tuten; Altay Gezer (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To determine the factors indicating the accuracy of fetal weight estimation in the last prenatal ultrasonography before delivery in preterm newborns with normal amniotic fluid volume.